Saving practices of single young Filipino professionals - Santos, Vangieliza C.; Bantang, Joanne R. (2006.)
This research is a qualitative study on the saving practices of single young Filipino professionals. It described their saving patterns in terms of the amount saved, reasons, regularity, and strategies for saving. The similarities and differences on the saving patterns in terms of age, gender, income, and position were also compared. Moreover, the research identified social network as an influence to their saving practices. Fifty respondents, with ages ranging from 21 to 35 years, were purposively chose to take part in the research. They were asked to answer a Saving Practices Scale related to their saving patterns. Ten respondents were further interviewed to clarify and validate the data from the initial survey. Results showed that 47 out of the 50 respondents save a part of their income mostly on a monthly basis. Their estimated average savings every year is Php 52, 396.74 and at least 36% have savings above the average annual savings of the Filipino family. The major reason for saving is to maintain regular savings for future use. Using content analysis of the respondents' answers, seven categories of saving strategies were created: money keeping or banking, planned buying, thrift eating, buying cheaper product substitute, practical buying, investing money, and using back up ("pa-libre"). It appears that the saving practices are influenced by demographic characteristics. as the person gets older, the amount of savings increases. Men and women differ in their saving strategies; men save through banking while women save by adequately planning things to buy. There are at least four sources of influences within the social network of young professionals. These are the family members, school- or work-related acquiantances, friends, and the significant other. Respondents also learn saving strategies from their own awareness of their experiences. It is recommended that comprehensive study regarding the savings and expenditures of young professionals be done. A negative case analysis is also recommended for those who do not save.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Savings and investments -- Philippines